Analisis Dampak Dana Desa dan Produk Domestik Regional Bruto Terhadap Indeks Pembangunan Manusia di Kabupaten Tapanuli Tengah - Sixson Roberto Simangunsong; Ahmad Albar Tanjung; Sabda Dian Nurani Siahaan (Forum Kerjasama Pendidikan Tinggi, 2021)
The village is the government agent at the forefront of implementing development, because development at the village level is directly related to the community. The Village Fund given to all villages in Tapanuli Regency provides hope for the realization of development in the village, The importance of making village communities as the main actors of development is supported that most of the village communities live in poverty and helplessness. The aim is to provide opportunities for regional capabilities and rural areas as the backbone of the regional and national economy. This research is grouped into quantitative research types. using time series data panel regression with human development index variables, village funds, and gross regional domestic product. The data analysis technique used is data analysis with quantitative methods with secondary data collection through the portal of the Central Bureau of Statistics of Central Tapanuli Regency. The results showed that the F-count value was 244.8101, with the village fund variable having a positive coefficient value of 0.042406 and t-count 0.539340, the gross regional domestic product was valued at 5.188551 with a t-count 11.91530, which means that the two variables had the same positive influence on the development index. In Tapanuli Tengah Regency, it is concluded that these two variables can increase the human development index in Central Tapanuli Regency